2014
DOI: 10.3174/ajnr.a3946
|View full text |Cite
|
Sign up to set email alerts
|

Brain Changes in Kallmann Syndrome

Abstract: BACKGROUND AND PURPOSE:Kallmann syndrome is a rare inherited disorder due to defective intrauterine migration of olfactory axons and gonadotropin-releasing hormone neurons, leading to rhinencephalon hypoplasia and hypogonadotropic hypogonadism. Concomitant brain developmental abnormalities have been described. Our aim was to investigate Kallmann syndrome-related brain changes with conventional and novel quantitative MR imaging analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
24
1
2
Order By: Relevance
“…While alterations in curvature-based measures have been detected in adult populations in association with dementia (Yin et al, 2014), genetic disorders (Manara et al, 2014), and degree of myelination (Shafee et al, 2015), we found only one curvature-based measure (positive shape index) associated with preterm birth despite differences in cortical folding visible on qualitative inspection of cortical surfaces. This may be related to the nature of the abnormality in preterminfants.…”
Section: Discussioncontrasting
confidence: 58%
“…While alterations in curvature-based measures have been detected in adult populations in association with dementia (Yin et al, 2014), genetic disorders (Manara et al, 2014), and degree of myelination (Shafee et al, 2015), we found only one curvature-based measure (positive shape index) associated with preterm birth despite differences in cortical folding visible on qualitative inspection of cortical surfaces. This may be related to the nature of the abnormality in preterminfants.…”
Section: Discussioncontrasting
confidence: 58%
“…All KS patients participated also to previous MRI studies [Manara et al, 2014[Manara et al, , 2015. We also scanned 24 healthy age-matched control subjects without MM.…”
Section: Experimental Designmentioning
confidence: 99%
“…In KS, anatomical and functional data rely on few neuroimaging studies [Koenigkam-Santos et al, 2008Krams et al, 1997Krams et al, , 1999Leinsinger et al, 1997;Manara et al, 2015;Mayston et al, 1997) that provided conflicting results. Preliminary findings on cortical-spinal tract or corpus callosum hypertrophy in KSMM1 versus KSMM- [Krams et al, 1999;Quinton et al, 1996] were not confirmed in subsequent larger series [Koenigkam-Santos et al, 2008, Manara et al, 2015; abnormal values of the magnetization transfer ratio at the pyramidal decussation were observed in KS patients regardless of the presence of MM [Koenigkam-Santos et al, 2010]; DTI analyses did not reveal structural changes of the cortical-spinal tract in both KSMM1 and KSMMpatients [Manara et al, 2014[Manara et al, , 2015 while T2 relaxation time was unilaterally increased in the right internal capsule posterior limb in spite of bilateral MM [Koenigkam-Santos et al, 2010]. Recently, by whole brain cortical thickness and voxel based morphometry analyses, KSMM1 showed, compared with KSMM-, significant cortical thinning in small regions known to be primarily involved in the voluntary hand motor control (e.g., the hand motor primary cortex) and bilateral volume decrease of the globus pallidus, thus disclosing a profound and complex structural reorganization of the motor circuit [Manara et al, 2015] associated to bimanual synkinesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, besides the association between OB aplasia/hypoplasia and an ipsilaterally decreased OS depth, further peculiar morphological and structural brain differences have been demonstrated in KS patients. New quantitative MRI analyses have shown surface cortical variations and gray matter and white matter density changes that clustered symmetrically in the frontal basal regions close to the OBs (gyrus rectus, medial orbitofrontal gyrus) . Even though these changes are thought to be induced by rhinencephalon underdevelopment, no study has investigated the relationship between OB volume and the contiguous forebrain cortex.…”
mentioning
confidence: 99%